Determinan Keputusan Pembelian Konsumen pada Produk Usaha Mikro Melalui Pendekatan Theory of Planned Behavior - Achmad Ridha; Fina Ruzika Zaimar; Wiwin Riski Windarsari; Hasisa Haruna; Adriansyah (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This study aims to analyze the factors that influence consumer purchasing decisions on micro-business products using the Theory of Planned Behavior (TPB) approach. The background of this study is based on the importance of understanding consumer behavior in the context of micro-businesses that play a significant role in the national economy, but still face challenges in identifying determinants of purchasing decisions scientifically. This study uses a quantitative approach with a survey technique by distributing questionnaires to 100 respondents who are consumers of micro-business products in Makassar City. Data were analyzed using multiple linear regression methods with the help of the SPSS version 29 program. The results showed that two of the three main TPB variables, namely attitudes and subjective norms, had a positive and significant effect on purchasing decisions, while perceived behavioral control did not have a significant effect. This finding supports Ajzen's theory (1991) and strengthens previous findings, especially that positive consumer attitudes and social support from the surrounding environment are the main determining factors in purchasing decisions. On the other hand, the insignificance of perceived behavioral control indicates that the aspect of ease or ability to buy is not always the main consideration, especially when the product is easily accessible. The conclusion of this study is that TPB is relevant to understand consumer behavior in the context of micro-enterprises, and can be a strategic basis for designing a marketing approach that is oriented towards consumer attitudes and social norms.